Binge drinking and illicit drug use among adolescent students - Jakelline Cipriano dos Santos Raposo; Ana Carolina de Queiroz Costa; Paula Andréa de Melo Valença; Patrícia Maria Zarzar; Alcides da Silva Diniz; Viviane Colares; Carolina da Franca (Revista de Saúde Pública, 2017)
ABSTRACT OBJECTIVE To estimate the prevalence of illicit drug use and its association with binge drinking and sociodemographic factors among adolescent students. METHODS This is a cross-sectional study with probabilistic conglomerate sampling, involving 1,154 students, aged 13 to 19 years old, from the public school system, in the city of Olinda, State of Pernambuco, Brazil, carried out in 2014. We used the Youth Risk Behavior Survey questionnaire, validated for use with Brazilian adolescents. The Chi-square test (≤ 0.05) and Poisson regression analysis were used to estimate the prevalence ratios, with 95% confidence intervals. RESULTS Use in life of illicit drugs was four times more prevalent among students who reported binge drinking (95%CI 3.19–5.45). Being in the age group of 16 to 19 years, being male, and having no religion were also significantly associated with illicit drug use. CONCLUSIONS The prevalence of use in life of illicit drugs was higher in this study than in other studies carried out in Brazil and it was strongly associated with binge drinking. This factor was associated with gender, age, and religion.